Legitimate Expectation in Administrative Procedure - Romić, Marko (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
Legitimate expectation is one of the basic procedural principles of the general administrative procedure codifications of many European countries. Having its foundation in Kantian philosophy, it was incorporated into the law of the European Union through the principle of legal certainty and the dominant influence of German legal theory. It is the Court of Justice of the EU that is responsible for the development of this principle in practice as well as the postulates on which its application in the member states is based. In 2016, the new Law on General Administrative Procedure in Serbia introduced the principle of foreseeability, which stipulates that administrative bodies, when resolving a specific administrative matter, are obliged to take into account their earlier decisions made in the same or similar matters. The question that arose was whether this meant that legitimate expectation was introduced into the legal order of Serbia, but under a different name? In the article, we will try to analyze the aforementioned issue, citing examples from comparative European practice, as well as stances from the judicial practice of the European Court of Justice. Special attention will be paid to the broadness of legitimate expectation, which in its core should protect the subjective public rights of legal entities, not just in administrative proceedings. The theoretical elaboration of the concept of legitimate expectations is important to reveal the essence of this concept, which does not solely imply specific actions in administrative/legal proceedings, but also during (by)law norming and the creation of public policies in certain social areas.